Efficacy of Aloe vera Gel on the Excision Wound Healing in Sprague dawley Rats: Efikasi Gel Lidah Buaya (Aloe vera) terhadap Kesembuhan Luka Eksisi pada Tikus Sprague dawley - Palgunadi, Bagus Uda; Rahayu, Asih; Prakoso, Yos Adi (Medicra (Journal of Medical Laboratory Science/Technology), 2021)
Wound is a pathological processes in all living things. Wound includes the overlapping mechanisms. The failure in wound healing causes infection. This study aimed to analyze the efficacy of Aloe vera gel in excisionwound on the rat’s back. This study used 18 male, Sprague Dawley rats, and they were induced excision wound on the back. The rats were separated into 3 groups, K1 = control, K2 = treated with betadin gel, K3 = treated with Aloe vera gel. The therapy was given twice a day for 7 days. The wound measurement was observed in day 3 and 7. The data were analyzed using SPSS. The result showed that Aloe vera gel potentially promote wound healing through the decrease microscopical condition of wound, re-epithelialization, and deposition of collagen better than in group K1 and K2 (p≤0.05). In conclusion, Aloe vera gel promote excision wound healing in Sprague Dawley rats.